(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The concept of the tragic is mostly developed and used in philosophical, aesthetic, culturological and literature works. The tragic is characterized as an aesthetic and metaphysical category, as a type of pathos, along with comic and dramatic, as mode of art, embodying the author’s concept of personality. In this paper, it is considered the essence and origins of the tragic, as well as its different understanding in antiquity and in modern times, which must be taken into account while analyzing this concept in modern theory of literature.